A Needle-Free Jet Injection System for Controlled Release and Repeated Biopharmaceutical Delivery - Mojiz Abbas Trimzi; Young-Bog Ham (Pharmaceutics, 2021)
Swift vaccination is necessary as a response to disease outbreaks and pandemics; otherwise, the species under attack is at risk of a high fatality rate or even mass extinction. Statistics suggest that at least 16 billion injections are administered worldwide every year. Such a high rate of needle/syringe injection administration worldwide is alarming due to the risk of needle-stick injuries, disease spread due to cross-contamination and the reuse of needles, and the misuse of needles. In addition, there are production, handling, and disposal costs. Needle phobia is an additional issue faced by many recipients of injections with needles. In addition to a detailed literature review highlighting the need for needle-free injection systems, a compressed air-driven needle-free jet injection system with a hydro-pneumatic mechanism was designed and developed by employing an axiomatic design approach. The proposed injection system has higher flexibility, uninterrupted force generation, and provides the possibility of delivering repeated injections at different tissue depths from the dermis to the muscle (depending on the drug delivery requirements) by controlling the inlet compressed air pressure. The designed needle-free jet injector consists of two primary circuits: the pneumatic and the hydraulic circuit. The pneumatic circuit is responsible for driving, pressurizing, and repeatability. The hydraulic circuit precisely injects and contains the liquid jet, allowing us to control the volume of the liquid jet at elevated pressure by offering flexibility in the dose volume per injection. Finally, in this paper we report on the successful design and working model of an air-driven needle-free jet injector for 0.2–0.5 mL drug delivery by ex vivo experimental validation.